Speedah-Cheetah : Binder of Doom #3 - Cummings, Troy (New York : Branches/Scholastic Inc., 2020)
It is time for the Stermont Derby, a race around downtown Stermont in homemade vehicles, and Alexander, Nikki, and Rip are planning to compete, but so is a new monster, a Speedah-cheetah--and in addition to a diet of rotten eggs it plans on eating the race losers, especially the members of the Super Secret Monster Patrol.
Ages 6-8.
K to Grade 3.
Keywords: Monsters -- Juvenile fiction; Soap box derbies -- Juvenile fiction; Best friends -- Juvenile fiction; Horror stories; Monsters -- Fiction; Soap box derbies -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Horror fiction